Musculoskeletal disorder symptoms in nurses and etiological factors: A cross-sectional research (Annals of Medical Research, 2021)
None
Keywords: key between March and June 2018. The population was composed of the 608 nurses working in the hospital. All of the population were invited to participate, and the research sample was formed from the 498 nurses who met the research inclusion criteria (participation rate 82%). Data were collected by researchers with technique of face-to-face interviews, using a nurse descriptive form and the Nordic Musculoskeletal Questionnaire. The data were analyzed using SPSS (Statistical Package for Social Sciences for Windows 16.0). Numbers, percentages, means and chi-squared tests were used in data analysis. The level of significance was set at 0.05.br /Result: The nurses’ mean age was 34.78±8.60 years (min: 18, max: 58) and most of them (75.5%) were females. The results showed that 87.3% of the nurses had reported MSDs symptoms in at least one body region during the past 12 months. The greatest prevalence of MSDs symptoms by body regions were in the lower back (78.5%), the back (74.9%), the knees (63.1%), the neck (61.2%) and the shoulders (59.6%). The study was found that MSDs symptoms were more frequently seen in those aged over 40, those who stated that their health was poor or very poor, those who had been working as nurses for more than 20 years, those with chronic illnesses, those who slept little, and those who worked more than eight hours a day or 40 hours a week (p0.05).br /Conclusion: This study showed that MSDs symptoms were common in nurses, the most frequent being discomfort of the back and lower back.br / Musculoskeletal disorder; Musculoskeletal system; Nurse; Pain; Symptom.